MOTIVASI BELAJAR BACA TULIS QUR’AN SISWA DI SMP ALFA SANAH - Wahyu Ningsih; Ayu Susilawati; Karina Adinda Wahyu Putri; Siti Hardiyanti (el-Moona: Jurnal Ilmu Pendidikan Islam, 2022)
Education of the holy book of the quran and studying it has a very important goal, including so that everything that is done must always be based on the guidance of the quran as the main reference source in the life of a believer. Therefore the importance of the quran to be studied, read, understood, internalized and practiced and everyday life. Motivation or enthusiasm for learning to read the quran is a driving force that arises both from outside and from a person or student who encourages them to carry out noble worship activities whose rewards are multiplied by Allah if they read them seriously and support an important role in giving passion, enthusiasm and a sense of pleasure to learn to read and write the quran. In this case, learning to read and write the quran in various educational institutation can make effective learning tools for student, so that they can provide maximum reading and writing learning outcomes. However, it was found that many factors became obstacles to success in learning to read and write the quran including the lack of student attention from both teachers and parents, inappropriate learning models and weakness student motivation for the material. On that basis, the author wants to examine the extent to which students motivation for learning at SMP Alfa Sanah is concerned in participating in learning to read and write the quran. Through this research, it is expected to be able to provide solutions, and to build student motivation especially at SMP Alfa Sanah so that student get maximum results of learning to read and write the quran.